Plague epidemic in 1649: nursing in the Hospital Five Wounds - José Robles Carrión; Francisco Javier Vega Vázquez; Estefanía Pachón María (Universidad de Alicante, 2012)
This article is a study of care applied in Seville in 1649, the hospital of the Five Wounds. Its aim is to present a stage of history, culture, society, politics and nursing in the seventeenth century Seville and promote reflection in relation to the conceptions of care this time, as exemplified by the Hospital of the Five Wounds. It is a descriptive, historical and critical-reflexive approach, the interpretation of the data followed the principles of content analysis. They concluded that unlike the rest of the healthcare team, the care team, you are not required academic professional requirements, also found that the end of the Hospital of the Five Wounds was to attend to women infected with diseases that are considered curable not contagious. Mortality due to this epidemic of plague, was very high, highlighting the actions in public health. We stress the importance of nursing staff in nursing education, the origin of a more organized teaching, later reflected in the Constitution of 1734.